Kajian Rancangan Rumah Murah Berbasis Biaya Konstruksi Sebagai Upaya Pemenuhan Kebutuhan Perumahan Bagi Masyarakat Menengah Ke Bawah (Rancang Bangun Rumah Pabrikan Dan Rumah Konvensional) - Wasino Wasino; Suwarto Suwarto; Triwardaya Triwardaya (Politeknik Negeri Semarang, 2017)
The needs of homes in Indonesia currently reach 6.5 million per year, the situation is of course not easily met by the developers for various reasons, ranging from purchasing power, and expensive building materials that impact on the concept of the house offered, which is simple, healthy and cheap. To achieve these criteria, it is necessary to innovate house planning in order to obtain competitive price, so that mthe price is affordable for lower middle class people. Currently Manufacturers offer the concept of home solutions in question, through the program